CO2-H2O MIXTURES IN THE GEOLOGICAL SEQUESTRATION OF CO2. II. PARTITIONING IN CHLORIDE BRINES AT 12-100°C AND UP TO 600 BAR - Spycher N.; Pruess K. (My University, 2005)
Correlations presented by Spycher et al. (2003) to compute the mutual solubilities of CO2 and H2O are extended to include the effect of chloride salts in the aqueous phase. This is accomplished by including, in the original formulation, activity coefficients for aqueous CO2 derived from several literature sources, primarily for NaCl solutions. Best results are obtained when combining the solubility correlations of Spycher et al. (2003) with the activity coefficient formulation of Rumpf et al. (1994) and Duan and Sun (2003), which can be extended to chloride solutions other than NaCl. This approach allows computing mutual solubilities in a noniterative manner with an accuracy typically within experimental uncertainty for solutions up to 6 molal NaCl and 4 molal CaCl2.